Responsibility for Reason-Giving: The Case of Individual Tainted Reasoning in Systemic Corruption - Ceva, Emanuela (Ethical theory and moral practice, 2018)
The paper articulates a new understanding of individual responsibility focused on exercises of agency in reason-giving rather than intentional actions or attitudes towards others. Looking at how agents make sense of their actions, we identify a distinctive but underexplored space for assessing individual responsibility within collective actions. As a case in point, we concentrate on reason-giving for one's own involvement in systemic corruption. We characterize systemic corruption in terms of its public 'unavowability' and focus on the redescriptions to which corrupt agents typically resort to vindicate their actions (e.g., when they present bribes as tokens of appreciation for services rendered). Through a multidimensional approach to reason-giving, we show that the individual rationalisations these redescriptions point to are necessarily less-than-successful since they keep thedifferent categories of reasons involved in making sense of one's own conduct misaligned. We argue that this involves a kind of tainted reasoning at the interface between epistemic vice and epistemic disadvantage. We then consider such test cases as self-deception, wilful ignorance, and actions on 'autopilot' to show that tainted reasoning is constitutive of systemic corruption, not merely caused by it. On this ground, we expound a new view of responsibility centred on reason-giving as the epistemic core which all responsibility assessments track. To demonstrate the interest of this view, we compare it with existing alternatives revolving around the ideas of accountability and attributability. We conclude by showing how our understanding of responsibility can shed new light on the analysis and normative assessment of an agent's responsible ignorance.